Development of bio-filament using hemp fiber for 3D-printer - Pullawan, Tanittha (Bulletin of Applied Sciences, 2022)
This work is a preliminary study about the use of hemp fiber as filler in a biopolymer, i.e. polylactic acid (PLA), and the following use of such composites in the 3D printing via FDM technique. In particular, hemp fiber (average length 150 micron) was added via melt-compounding into PLA 2003D at different weight percentages (1, 2.5, 5 and 10%wt). We observed that not only tensile strength increased with the increased of hemp fiber content, but also increase in brittleness. Moreover, PLA/1%wt hemp fiber was chosen to study the optimal amount of plasticizer. To solve the brittleness problem, we adjust the flexibility of the material by adding the plasticizer Polyethylene glycol (PEG) ratio 2.5 and 5%wt, respectively. The results showed a remarkable increase in the elongation at break of material, which is a necessary feature to form a 3D printed filament for 3D printing.